2020
DOI: 10.31234/osf.io/27fy6
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COnVida-20(1)

Abstract: An increasing number of studies have addressed the psychological impact of the COVID-19 crisis in the general population. Nevertheless, far less is known about the impact in specific populations such as university students, whose psychological vulnerability has been shown in previous research. This study sought to examine different indicators of mental health in university students during the Spanish lockdown; we also analyzed the main sources of stress perceived by students in relation to the COVID-19 crisis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…All the processes presented values for h° within the range from 270.18° to 292.09°, values higher than those obtained using non-pressurized and CE processes. Considering the cylindrical chromatic space CIE-L* C* hº system proposed by Padrón et al (2012) as the reference, the hue angles correspond to a blue-violet color. In vitro study of the antioxidant activities of the purple corn cob extracts obtained by DHP The methodologies used revealed that the AA values of the purple corn cob extracts obtained by DHP were significantly higher than the values in the extracts obtained by CE, results which are consistent considering that the extracts obtained using highpressure presented higher TPC contents (Jurić et al, 2019).…”
Section: Characterization Of the Purple Corn Cob Powdermentioning
confidence: 99%
“…All the processes presented values for h° within the range from 270.18° to 292.09°, values higher than those obtained using non-pressurized and CE processes. Considering the cylindrical chromatic space CIE-L* C* hº system proposed by Padrón et al (2012) as the reference, the hue angles correspond to a blue-violet color. In vitro study of the antioxidant activities of the purple corn cob extracts obtained by DHP The methodologies used revealed that the AA values of the purple corn cob extracts obtained by DHP were significantly higher than the values in the extracts obtained by CE, results which are consistent considering that the extracts obtained using highpressure presented higher TPC contents (Jurić et al, 2019).…”
Section: Characterization Of the Purple Corn Cob Powdermentioning
confidence: 99%